Pathway-directed therapy in multiple myeloma - John, Lukas; Krauth, Maria Theresa; Podar, Klaus; Raab, Marc-Steffen (Cancers, 2021)
Multiple Myeloma (MM) is a malignant plasma cell disorder with an unmet medical need, in particular for relapsed and refractory patients. Molecules within deregulated signaling pathways, including the RAS/RAF/MEK/ERK, but also the PI3K/AKT-pathway belong to the most promising evolving therapeutic targets. Rationally derived compounds hold great therapeutic promise to target tumor-specific abnormalities rather than general MM-associated vulnerabilities. This paradigm is probably best depicted by targeting mutated BRAF: while well-tolerated, remarkable responses have been achieved in selected patients by inhibition of BRAFV600E alone or in combination with MEK. Targeting of AKT has also shown promising results in a subset of patients as monotherapy or to resensitize MM-cells to conventional treatment. Approaches to target transcription factors, convergence points of signaling cascades such as p53 or c-MYC, are emerging as yet another exciting strategy for pathway-directed therapy. Informed by our increasing knowledge on the impact of signaling pathways in MM pathophysiology, rationally derived Precision-Medicine trials are ongoing. Their results are likely to once more fundamentally change treatment strategies in MM.